Nilai Budaya dan Historis Bangunan Museum Keraton Sumenep sebagai Muatan Karakter Profil Pelajar Pancasila - Aji Saputra, Mochammad Ronaldy; Gede Agung, Dewa Agung; Efendi, Agik Nur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Society has a journey of cultural and historical values. Museums have a role in preserving the heritage of cultural and historical values ​​through their collections. The heritage of cultural and historical values ​​in the museum has a character load that has implications for strengthening the character Profil Pelajar Pancasila which can be taught to future generations. This makes researchers want to develop the concept of cultural and historical values ​​which have implications for the character content of Profil Pelajar Pancasila at one of the museums in Madura, the Sumenep Palace Museum with grounded theory. The data collection method used theoretical sampling, collected through observation, literature study, documentation, and interviews. The data analysis technique consists of 3 stages, namely open coding, axial coding, and selective coding. The results show that the Sumenep Palace Museum has cultural values ​​both intangible and tangible. Intangibles tend to lead to leadership values ​​that must be possessed by leaders, namely intellectuality, spiritual attitude (sokkla), andhap asor (humble), openness, and civility. Then tangibles can be taken from the buildings in the Sumenep Palace Museum complex. Historical values ​​can be taken from the court figures of the Sumenep Palace, such as Bindara Saod, Panembahan Somala, and Sultan Abdurahman Pakunataningrat. Cultural and historical values ​​will always be integrated into shaping the character of Profil Pelajar Pancasila so that what is contained in the Sumenep Palace Museum becomes a teaching medium. Through these lessons, future generations admire the work created by the kings of Sumenep and provide inspiration that they have been able to produce a work.